Acute Myocardial Injury Detected By ECG-Synchronized Perfusion Single-Photon Emission Computed Tomography in a Polymorbid Female Patient - E. N. Ostroumov; A. A. Kanibolotsky; E. V. Migunova; N. Y. Kudryashova; E. V. Stepan; D. A. Chepky; R. S. Muslimov; M. V. Parkhomenko; S. Y. Kambarov; M. K. Mazanov; O. G. Sinyakova (Неотложная медицинская помощь)
A case of acute focal myocardial injury in a polymorbid female patient with intact coronary arteries according to direct coronary angiography is reported. Acute focal myocardial injury was detected by ECG-synchronized  perfusion single-photon emission computed tomogra-phy (SPECT) of the  myocardium, and confirmed by the results of postmortem examination. The article also discusses the possibility of using perfusion SPECT to diagnose acute focal changes against the background of focal inflammatory myocardial infiltration.